2007
DOI: 10.1093/intimm/dxm014
|View full text |Cite
|
Sign up to set email alerts
|

Activation-induced FOXP3 in human T effector cells does not suppress proliferation or cytokine production

Abstract: Forkhead box P3 (FOXP3) is currently thought to be the most specific marker for naturally occurring CD4(+)CD25(+) T regulatory cells (nTregs). In mice, expression of FoxP3 is strictly correlated with regulatory activity, whereas increasing evidence suggests that in humans, activated T effector cells (Teffs) may also express FOXP3. In order to better define the role of FOXP3 in human Teff cells, we investigated the intensity and kinetics of expression in ex vivo Teff cells, suppressed Teff cells and Teff cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
655
10
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 769 publications
(724 citation statements)
references
References 38 publications
51
655
10
8
Order By: Relevance
“…It is a transcription factor critical for the development and function of regulatory T cells [30][31][32][33], and its expression is generally considered to define Tregs with suppressive capability [31][32][33][34]. On the other hand, in recent studies it became clear that the role of human FOXP3 is different from that of its murine counterpart, being a consequence of activation status, and responsible for an anergic phenotype, but not necessarily for a regulatory function of cells that express it [4,26,28,[34][35][36]. Nevertheless, a suppressive capacity of CD4 + CD25 high FOXP3 + cells isolated from human tumors was demonstrated by Kryczek et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is a transcription factor critical for the development and function of regulatory T cells [30][31][32][33], and its expression is generally considered to define Tregs with suppressive capability [31][32][33][34]. On the other hand, in recent studies it became clear that the role of human FOXP3 is different from that of its murine counterpart, being a consequence of activation status, and responsible for an anergic phenotype, but not necessarily for a regulatory function of cells that express it [4,26,28,[34][35][36]. Nevertheless, a suppressive capacity of CD4 + CD25 high FOXP3 + cells isolated from human tumors was demonstrated by Kryczek et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed a number of groups have noted a reduction of CD4 1 CD25 hi Treg in SLE [54,55]. FOXP3 expression is known to be increased upon activation of human T cells [56][57][58]. However, the increased numbers of CD4 1 FOXP3 1 T cells found in autoimmune inflammatory environments such as EAE or the rheumatoid joint [59][60][61] has been used to support the argument that Treg are expanded in inflammation but are unable to establish control [62].…”
Section: Discussionmentioning
confidence: 99%
“…The follicular group was defined as the population of Foxp3 þ cells that mainly occupied lymphoid follicles of the submucosal layer compared to any other region of the tumour (original magnification: Â 4, Â 40). (Zheng et al, 2004;Fontenot et al, 2005;Allan et al, 2007;Pillai et al, 2007). Recently, it has been reported that Foxp3, forkhead/winged helix transcription factor, is the most reliable marker of T regs Yagi et al, 2004;Fontenot et al, 2005).…”
Section: Discussionmentioning
confidence: 99%